Empty simplices of large width - Joseph Doolittle; Lukas Katthän; Benjamin Nill; Francisco Santos (Forum of Mathematics, Sigma, 2025)
An empty simplex is a lattice simplex in which vertices are the only lattice points. We show two constructions leading to the first known empty simplices of width larger than their dimension: